2021
DOI: 10.3389/fonc.2021.737943
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trials of the BTK Inhibitors Ibrutinib and Acalabrutinib in Human Diseases Beyond B Cell Malignancies

Abstract: The BTK inhibitors ibrutinib and acalabrutinib are FDA-approved drugs for the treatment of B cell malignances. Both drugs have demonstrated clinical efficacy and safety profiles superior to chemoimmunotherapy regimens in patients with chronic lymphocytic leukemia. Mounting preclinical and clinical evidence indicates that both ibrutinib and acalabrutinib are versatile and have direct effects on many immune cell subsets as well as other cell types beyond B cells. The versatility and immunomodulatory effects of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 206 publications
(416 reference statements)
0
17
0
Order By: Relevance
“…TLRs, NLRP3, TREM-1, and Dectin-1 can activate monocytes, macrophages, and neutrophils, and ibrutinib can block this activation through BTK-dependent processes. Ibrutinib can also inhibits T-cell differentiation, effector function, and survival by inhibiting IL-2-inducible T-cell Kinase (ITK) on T-cells [ 30 ]. A recent in vitro study has also demonstrated that ibrutinib-associated BTK depletion impairs NFAT and NF-κB responses in macrophages, leading to impaired clearance of Aspergillus fumigatus [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…TLRs, NLRP3, TREM-1, and Dectin-1 can activate monocytes, macrophages, and neutrophils, and ibrutinib can block this activation through BTK-dependent processes. Ibrutinib can also inhibits T-cell differentiation, effector function, and survival by inhibiting IL-2-inducible T-cell Kinase (ITK) on T-cells [ 30 ]. A recent in vitro study has also demonstrated that ibrutinib-associated BTK depletion impairs NFAT and NF-κB responses in macrophages, leading to impaired clearance of Aspergillus fumigatus [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that BTK is a key mediator of innate immunity and inflammation ( Weber et al, 2017 ; Weber, 2021 ) strongly suggest that TBBPA has the potential to lead to a strong imbalance, which in turn could induce and/or aggravate damages to the BBB integrity ( Ní Chasaide and Lynch, 2020 ), and permeate TBBPA in the central nervous system with more direct effects. Of note, BTK inhibitor share a variety of clinical applications, ranging from treatment of B cell malignancies, to autoimmune diseases and COVID-19 ( Zhu et al, 2021 ; Malekinejad et al, 2022 ; Rezaei et al, 2022 ; Weis et al, 2022 ), which raise the question on whether TBBPA may interfere with these therapeutic actions. This will certainly require dedicated experimental exploration and validation.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al present a comprehensive review on their effect on a variety of immune cell subsets besides B cells, and illustrated their impact on BTK-dependent and -independent signaling. Given their broad effect, one can envision that they could be integrated into combinatory regimens to ameliorate autoimmune damage and/or to boost antitumor immunity (Zhu et al, 2021).…”
Section: Editorial On the Research Topicmentioning
confidence: 99%